Breaking the Silence: A Content and Expert Analysis of the 2025 Ramadan series Lam Shamseya's Framing and Subversion of Child Sexual Abuse Discourse in Egypt - Abouelnasr, Maya (AUC Knowledge Fountain, 2026)
This thesis analyzes how the 2025 Egyptian TV series Lam Shamseya served as a sociocultural intervention and awareness platform for reframing and subverting the typical child sexual abuse (CSA) discourse in Egypt. Using a mixed-methods approach, the study triangulates framing theory and two complementary tools of the critical discourse analysis (CDA) and the circuit of culture model through a scene-level content analysis of 304 scenes across all 15 episodes of the series and ten semi-structured interviews with media experts, media practitioners, and psychologists. Key findings include reported corroboration of subversion of traditional tropes and archetypes, as well as reframing of CSA understanding through deeper analysis of characterization, visual affinity, subject-position shifts, and the embedded edutainment mechanisms. Meanwhile, the expert interviews filled gaps in the existing literature surrounding the Egyptian television industry, as well as providing specialized in-depth assessments into media treatment of the series and observed real-life outcomes. This research contributes to the field of mass communication by providing an extensive English-language analysis of the series for a wider audience and analyzing how edutainment messaging has great potential to catalyze legal and social changes in a collectivistic society where a culture of silence surrounding both child sexual abuse and sexual abuse had long been normalized.